Air pollution due to road traffic in Ljubljana - Ogrin, Matej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
Air pollution is due to road traffic an inevitable outcome of internal combustion in engines of vehicles and some other processes. Air near the roads is more polluted with some pollutants, such as carbon monoxide, nitrogen oxides, ozone, particulate matter and some others. Monitoring the air quality is a key issue, when one wants to estimate environmental impacts of the road traffic. The article shows a method of passive samplers for air quality monitoring along different roads in the area of Ljubljana Municipality.
Keywords: Ljubljana; cestni promet; onesnaževanje; onesnaževanje zraka; onesnaženost zraka; ecology; ekologija